2023
DOI: 10.1097/xcs.0000000000000554
|View full text |Cite
|
Sign up to set email alerts
|

Myoglobinemia, Peripheral Arterial Disease, and Patient Mortality

Abstract: BACKGROUND: Peripheral arterial disease (PAD) causes leg muscle damage due to inadequate perfusion and increases cardiovascular events and mortality 2- to 3-fold. It is unclear if PAD is a biomarker for high-risk cardiovascular disease or if skeletal muscle injury harms arterial health. The objective of this work is to test if serum myoglobin levels (myoglobinemia) are a marker of PAD, and if so, whether myoglobin impairs vascular health. STUDY DESIGN: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Additionally, myoglobin may be involved in the recruitment and activation of immune cells, such as macrophages, which play a role in the inflammatory response associated with atherosclerosis. The exact mechanisms by which myoglobin influences atherosclerosis are not fully understood, and research in this area is ongoing [64][65][66]. Troponin T (Figure 4) is a protein primarily known for its role in muscle contraction, particularly in cardiac muscle.…”
Section: Biomarkers In Atherosclerosismentioning
confidence: 99%
“…Additionally, myoglobin may be involved in the recruitment and activation of immune cells, such as macrophages, which play a role in the inflammatory response associated with atherosclerosis. The exact mechanisms by which myoglobin influences atherosclerosis are not fully understood, and research in this area is ongoing [64][65][66]. Troponin T (Figure 4) is a protein primarily known for its role in muscle contraction, particularly in cardiac muscle.…”
Section: Biomarkers In Atherosclerosismentioning
confidence: 99%
“…At the biochemical level the myopathy is characterized by oxidative damage, mitochondrial dysfunction, cytoskeletal disintegration and upregulation of cytokines [15][16][17][18]20,21,25,26,[29][30][31][32][33][34][35][36][37] . Work from several laboratories including our own has demonstrated that this myopathy is closely related to leg function, daily activity, quality of life and mortality of PAD patients [38][39][40][41][42][43][44][45][46] . In regards to mortality, our group recently demonstrated 47 that two basic biochemical biomarkers of PAD myopathy, protein concentration and mitochondrial content in gastrocnemius biopsies, are predictors of 5-year mortality in PAD patients.…”
mentioning
confidence: 94%